ANALISIS KEGUNAAN DAN KEBERMANFAATAN APLIKASI GRABFOOD DI WILAYAH PALEMBANG MENGGUNAKAN REGRESI LINIER SEDERHANA - marsa silvia, Mutiara; M wirayuda; Tata Sutabri (J-ENSITEC, 2024)
The development of information and communication technology has brought significant changes in various aspects of people's lives, including consumption and food services. One of these advances is the presence of food delivery service applications, such as GrabFood. This research aims to analyze the usability and usefulness of the GrabFood application in the Palembang area using a simple linear regression method. Data was obtained through a survey of GrabFood application users in Palembang. The independent variable is application usability, measured based on ease of use, accessibility, and speed of service. The dependent variable is the usefulness of the application, measured based on the level of user satisfaction and frequency of use. The results of the analysis show a significant positive relationship between usability and usefulness on the attitudes of GrabFood application users. In conclusion, increasing the usability of the GrabFoodapplication increases its usefulness for users in Palembang. This research has implications for developing and improving GrabFood application services to better meet user needs and expectations.